O potencial de um estudo piloto na pesquisa qualitativa (The potential of a pilot study in qualitative research) - Silva Filho, Analdino Pinheiro; Barbosa, Jonei Cerqueira (Revista Eletrônica de Educação, 2019)
In this paper, it is discuss the points raised from a pilot study for qualitative research planning. The argumentation present here is the result of a pilot study that focused the games of mathematical language on teacher training for rural schools. The data production took place in the Federal University of Reconcâvo Baiano, campus of Feira de Santana, state of Bahia, Brazil. The pilot study did not only provide insights for the research, but for any qualitative inquiry. Based on that, it is suggest that pilot study raises questions for reviewing a qualitative research planning in at least six dimensions: ethical, methodological, theoretical, analytical, operational and representational. Resumo Neste artigo, são discutidas as potencialidades do estudo piloto para o desenvolvimento da pesquisa qualitativa. A argumentação ora apresentada é fruto de um estudo piloto que focalizou os jogos de linguagem matemáticos na formação de professores do campo. A produção de dados ocorreu no curso de Licenciatura em Educação do Campo com Habilitações em Ciências da Natureza e Matemática em uma universidade pública no interior da Bahia, Brasil. O estudo piloto dessa pesquisa não gerou insights apenas para o delineamento da referida pesquisa, mas para qualquer investigação qualitativa. Baseado nisso, argumenta-se que o estudo piloto levanta questões para o refinamento do planejamento da pesquisa, pelo menos, em seis dimensões: ética, metodológica, teórica, analítica, operacional e representacional. Keywords: Pilot study, Qualitative research, Research Planning. Palavras-chave: Estudo piloto, Pesquisa qualitativa, Planejamento da pesquisa. References ARAIN, Mubashir et al. What is a pilot or feasibility study? A review of current practice and editorial policy. BMC Medical Research Methodology. UK, jul. 2010. Disponível em: <https://bmcmedresmethodol.biomedcentral.com/track/pdf/10.1186/1471-2288-10-67>. Acesso em: 21 set. 2017. ARNOLD, Donald et al. The design and interpretation of pilot trials in clinical research in critical care. Crit Care Med. USA, vol. 37, n. 1, jan. 2009. Disponível em: <http://citeseerx.ist.psu.edu/viewdoc/download?doi=10.1.1.622.1427&rep=rep1&type=pdf>. Acesso em 22 set. 2017. BELLO, Samuel Edmundo Lopez; RÉGNIER, Jean-Claude. Linguagem, realidade e subjetividade: elementos para uma Educação Matemática contemporânea. In: JELINEK, Karin Ritter; BELLO, Samuel Edmundo Lopez; SANTOS, Suelen Assunção (Orgs.). Educação Matemática: linguagens, práticas e sujeitos. Porto Alegre: Editora Canto - Cultura e Arte, p. 25-41, 2017. Disponível em: <http://canto.art.br/wp-content/uploads/2018/05/Educacao-Matematica-linguagens-praticas-e-sujeitos-versao-digital-espelhada.pdf>. Acesso em: 6 abr. 2019 BIRMAN, Joel. Jogando com a Verdade. Uma Leitura de Foucault. PHYSIS: Revista Saúde Coletiva, Rio de Janeiro, v. 12, n.2, p.301-324, 2002. Disponível em: < http://www.scielo.br/pdf/physis/v12n2/a07v12n2.pdf>. Acesso em: 5 abr. 2019. BRASIL. Ministério da Educação. Projeto Pedagógico do Curso de Licenciatura em Educação do Campo com Habilitações em Ciências da Natureza e Matemática. Feira de Santana: Coordenadoria de Ensino e Integração Acadêmica. CETENS/UFRB, 2013. CREPALDE, Rodrigo Santos; KLEPKA, Verônica; PINTO, Tânia Halley Oliveira. Interculturalidade e conhecimento tradicional sobre a Lua na formação de professores no/do campo. Revista Brasileira de Educação do Campo, Tocantinópolis, v. 2, n. 3, p. 836-860, jul./dez., 2017. Disponível em: <https://doi.org/10.20873/uft.2525-4863.2017v2n3p836>. Acesso em: 5 maio 2017. CRESWELL, John. W. Investigação Qualitativa e Projeto de Pesquisa: escolhendo entre cinco abordagens. 3 ed. Porto Alegre: Penso, 2014. 341 p. DANNA, Cristiane Lisandra. O teste piloto: uma possibilidade metodológica e dialógica na pesquisa qualitativa em educação. In: I COLÓQUIO NACIONAL E VII ENCONTRO DO NÚCLEO DE ESTUDOS LINGUÍSTICOS (NEL) da FURB, 16, 2012, Blumenau. Anais eletrônicos. Blumenau: FURB, 2012. Disponível em: <https://www.tecnoevento.com.br/nel/anais/artigos/art16.pdf>. Acesso em: 21 set. 2017. DE VAUS, David. Surveys in Social Research - 3rd edn. London: UCL Press, 1993. 379 p. FLICK, Uwe. Introdução à Pesquisa Qualitativa. 3. ed. Porto Alegre: Bookman, 2009. 405 p. FONGER, Nicola. Lessons learned as a novice researcher: A pilot study in Mathematics Education. The Hilltop Review, Michigan, apr. 2011. Disponível em: <https://scholarworks.wmich.edu/cgi/viewcontent.cgi?article=1040&context=hilltopreview>. Acesso em: 6 fev. 2018. FOUCAULT, Michel. O cuidado com a verdade. In: FOUCAULT, Michel. Ditos e Escritos V. Ética, Sexualidade e Política. Rio de Janeiro: Forense Universitária, 2004c, p. 240-251. FOUCAULT, Michel. A Ordem do Discurso. Trad. Laura Fraga de Almeida Sampaio. 24 ed. São Paulo: Loyola, 2014. 74 p. GAIA, C.; PIRES, L. Saberes matemáticos e história de vida na zona rural de Marabá-PA. Revista Brasileira de Educação do Campo, Tocantinópolis, v. 1, n. 1, p. 128-146, jan./jun.,2016. Disponível em: < https://doi.org/10.20873/uft.2525-4863.2016v1n1p128>. Acesso em: 5 mai 2017. GLOCK, Hans-Johann. Dicionário de Wittgenstein. Rio de Janeiro: Zahar, 1998. 398 p. GRIX, Jonathan. The Foundations of Research. New York: Palgrave Study Skills, 2004. 200 p. GROS, Frédéric; DAVIDSON, Arnold. Foucault, Wittgenstein: de possibles rencontres. Paris: Éditions Kimé, 2011. ISMAIL, Nashwa; KINCHIN, Gary. EDWARDS, Julie-Ann. Pilot study, does it really matter? Learning lessons from conducting a pilot study for a qualitative PhD Thesis. International Journal of Social Science Research. USA, mar. 2018. Disponível em: <http://www.macrothink.org/journal/index.php/ijssr/article/view/11720/9594>. Acesso em: 8 fev. 2018. JANGHORBAN, Roksana; ROUDSARI, Robab Latifnejad; TAGHIPOUR, Ali. Pilot study in qualitative research: the roles and values. Journal of Hayat, Tehran, mar. 2014. Disponível em: <http://hayat.tums.ac.ir/browse.php?a_id=666&sid=1&slc_lang=en>. Acesso em: 6 fev. 2018. KIM, Yujin. The pilot study in qualitative inquiry: identifying issues and learning lessons for culturally competent research. Qualitative Social Work, USA, may 2011. Disponível em: <https://doi.org/10.1177/1473325010362001>. Acesso em: 6 fev. 2018. KNIJNIK, Gelsa. Differentially positioned language games: ethnomathematics from a philosophical perspective. Educational Studies in Mathematics, Switzerland, v. 80, p. 87-100, may 2012. Disponível em: <https://link.springer.com/article/10.1007/s10649-012-9396-8>. Acesso em: 10 mar 2018. KNIJNIK, Gelsa. Etnomatemáticas en movimiento: Perspectiva Etnomatemática, sus formulaciones teóricas y ejemplificaciones. Revista Latinoamericana de Etnomatemática, Colombia, v. 7, n. 2, p. 139-151, jun./sep. 2014. Disponível em: <http://www.revista.etnomatematica.org/index.php/RevLatEm/article/view/127>. Acesso em: 5 abr. 2019. KNIJNIK, Gelsa. A ordem do discurso da matemática escolar e jogos de linguagem de outras formas de vida. Perspectivas da Educação Matemática, Campo Grande, v. 10, n. 22, p. 45-64, 2017. Disponível em: <http://seer.ufms.br/index.php/pedmat/article/view/3877/3104>. Acesso em: 10 mar 2018. MACKEY, Alison; GASS, Susan. Second language research: methodology and design. New Jersey: Lawrence Erlbaum Associates, 2005. 405 p. RICHARDSON, Roberto Jerry. Pesquisa social: métodos e técnicas. 3. ed. São Paulo: Atlas, 2012. 394 p. SILVEIRA, Maria Rosâni Abreu. Matemática, discurso e linguagens: contribuições para a Educação Matemática. São Paulo: Editora Livraria da Física, 2015. (Coleção Contextos da Ciência). TEIJLINGEN, Edwin Van; HUNDLEY, Vanora. The importance of pilot studies. Social Research Update. England, jan./mar. 2001. Disponível em: <http://sru.soc.surrey.ac.uk/SRU35.html>. Acesso em: 5 fev. 2018. THABANE, Lehana et al. A tutorial on pilot studies: the what, why and how. BMC Medical Research Methodology. London, jan. 2010. Disponível em: <https://www.ncbi.nlm.nih.gov/pmc/articles/PMC2824145/>. Acesso em: 7 fev. 2018. UNIVERSIDADE FEDERAL DO RECÔNCAVO DA BAHIA. Projeto Pedagógico do Curso de Licenciatura em Educação do Campo com Habilitações em Ciências da Natureza e Matemática. Feira de Santana, 2013. VEIGA-NETO, Alfredo. Foucault & a Educação. 2 ed. Belo Horizonte: Autêntica, 2007. (Coleção Pensadores & Educação). VEIGA-NETO, Alfredo. Teoria e método em Michel Foucault: (im)possibilidades. Cadernos de Educação. Pelotas, n. 34, p. 83 - 94, set./dez., 2009. Disponível em: <https://periodicos.ufpel.edu.br/ojs2/index.php/caduc/article/view/1635/1518>. Acesso em: 6 abr. 2019. VERGÈS, P. Ensemble de Programmes Permettant L’annalyse des Évocations – EVOC 2000. Manuel, version, 5. 2002. WANDERER, Fernanda. Educação Matemática, jogos de linguagem e regulação. São Paulo: Livraria da Física, 2014. (Coleção Contextos da Ciência). WANDERER, Fernanda. Educação Matemática, processos de regulação e o Programa Escola Ativa. Revista de Educação Pública. Cuiabá, v. 26, n. 61, p. 201-221, jan./abr., 2017. Disponível em: <http://periodicoscientificos.ufmt.br/ojs/index.php/educacaopublica/article/view/2397/pdf>. Acesso em: 6 abr. 2019 WITTGENSTEIN, Ludwig. Investigações Filosóficas. Trad. Marcos G. Nontagnoli. 6. ed. São Paulo: Vozes, 2009. 350 p. WRAY, Jane; ARCHIBONG, Uduak; WALTON, Sean. Why undertake a pilot in a qualitative PhD study? Lessons learned to promote success. Nurse Researcher. Ontário, jan. 2017. Disponível em: <https://www.researchgate.net/publication/312593847_Why_undertake_a_pilot_in_a_qualitative_PhD_study_Lessons_learned_to_promote_success>. Acesso em: 8 fev. 2018.